2011
DOI: 10.7748/ns2011.06.25.40.39.c8565
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the learning experiences of nursing students with dyslexia

Abstract: Nursing students with dyslexia may benefit from sharing placement experiences with colleagues outside the clinical environment. They may also benefit from receiving support from their placement mentor and a representative from the university who knows about dyslexia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(57 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…It is worthy of note that studies of nursing students with dyslexia show similar results to this study (Child & Langford, ; Morris & Turnbull, ). And another study of five people with dyslexia in Malaysia (Oga & Haron, ) reported the following main theme clusters: subjected to the watchful eyes of others and their negative reactions; receiving support; encountering difficulties in academic‐related areas; reactions towards the condition of being dyslexic; poor sense of orientation; and areas of strength and/or passion. …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is worthy of note that studies of nursing students with dyslexia show similar results to this study (Child & Langford, ; Morris & Turnbull, ). And another study of five people with dyslexia in Malaysia (Oga & Haron, ) reported the following main theme clusters: subjected to the watchful eyes of others and their negative reactions; receiving support; encountering difficulties in academic‐related areas; reactions towards the condition of being dyslexic; poor sense of orientation; and areas of strength and/or passion. …”
Section: Discussionsupporting
confidence: 89%
“…These struggles with timekeeping could be linked to Child and Langford's finding of reduced short‐term memory capabilities in nursing students with dyslexia. This study also highlighted the difficulty of adjusting to different work routines when starting new clinical placements (Child & Langford, ). We could not locate any research into this area concerning medical students.…”
Section: Introductionmentioning
confidence: 87%
“…Furthermore, the position taken up by students on the 'Embrace, Passive Engag-er, Resist' (EPER) continuum is influenced possibly by discourses students draw on in framing their dyslexic identity. Students embracing the identity collectively were noted as being equipped in accessing learning and teaching (Goode 2007) and identifying supports (Child & Langford 2011, Storr et al 2011. These students appear to refuse to internalize negative constructions of their dyslexic identity and furthermore were not preoccupied with how they were viewed by nurse preceptors.…”
Section: Discussionmentioning
confidence: 98%
“…The adverse effects of stigma associated with disclosure and accessing academic supports can manifest (Roberts et al 2009). Evidence of unsupportive learning atmospheres (White 2007), judgemental (Child & Langford 2011) and negative attitudes (Illingworth 2005) of staff towards those with dyslexia in nurse education reinforces the importance for students in getting a decision on disclosure correct.…”
Section: Constructed Dyslexia Identitiesmentioning
confidence: 99%
“…10,11 Dyslexia is similarly well documented in the world of nursing education. 12,13 Although many authors confl ate dyslexia and dyspraxia in their research, there is little research considering the unique experiences of those with dyspraxia in health care education. 6,9 Anecdotal evidence suggests that clinical educators may have a limited understanding of dyslexia, and even less understanding of dyspraxia.…”
Section: Discussionmentioning
confidence: 99%